MEASURING CARBON DISCLOSURE FROM CEO CHARACTERISTICS - Harjito, Yunus; Sutopo, Bambang (JURNAL AKUNTANSI DAN AUDITING, 2024)
This study aims to examine the influence of CEO characteristics with the proxies used, namely gender, foreign CEOs, and CEO impression management on carbon disclosure. The study takes data on mining sector companies listed on the Indonesia Stock Exchange with a coverage of 2019 to 2023 which includes 68 companies with a total of 340 data. The results showed that all CEO characteristics used in this study proved to have a positive and significant effect on carbon disclosure. The presence of a female CEO leading the company will improve the quality and environmental performance of the company, as well as carbon disclosure. In addition, the presence of foreign CEOs who have a foreign educational background also has a positive impact on corporate carbon disclosure. The narcissistic nature shown by CEOs in company reports through CEO impression management is also proven to have a positive and significant impact on carbon disclosure. All the results of this study are proven to confirm the statements contained in the upper echelon theory.